CARDIOGENIC SHOCK ETIOLOGY, CLINIC, EXAMINATION METHODS AND MODERN METHODS OF TREATMENT - Doniyorov Shaxzod; Shernazarov Sardor; Yavgashev Asomiddin (Journal of Science in Medicine and Life, 2024)
Cardiogenic shock is life-threatening. Often this is caused by a heart attack. Cardiogenic shock is life-threatening, with a high mortality rate of 30 to 50 percent. This means that almost every second person will not experience a heart attack. However, in recent years, the chance of survival has increased due to improved treatment. The most important thing is to open the blocked coronary artery as soon as possible and restore blood flow and oxygen supply. Those who survive the first 30 days after cardiogenic shock have a good chance of long-term survival.